Soft infrastructure: the critical community-level resources reportedly needed for program success - Shane A Kavanagh; Penelope Hawe; Alan Shiell; Mark Mallman; Kate Garvey (BMC, 2022)
Abstract Background The mechanisms typically used to fund health promotion in communities, either as part of an effort to scale-up programs or to support the design of local activities, often pay insufficient attention to the foundational means of enhancing well-being. Only recently have researchers begun to critically 'unpack' how funding processes connect with and activate local community capacities. Methods We conducted a thematic analysis of 33 interviews with policy and program administrators in public health and local community workers and volunteers. We invited them to expound on their understandings of resources - specifically, what needs to be in place to make funded programs successful and/or what do communities draw on to make funded programs effective. Results Policy and program administrators reflected mostly on the importance of traditional resources, such as adequate funding and staffing. Community-based participants often went further to describe psychological and sociological resources - the "soft infrastructure" which included trust and hope. Both groups emphasised the importance of building networks and relationships at multiple levels. Community workers also provided examples of how resources grow and improve in value in combination with other processes or through pathways of resource use or resource distribution. So, resources like information/knowledge are made more valuable when relayed locally. Physical amenities (e.g., meeting spaces, kitchens) have an instrumental role, but also act powerfully as a symbolic resource for identity. Participants reported that funding processes can damage the resources required for community health improvement. Funding instability undermines capacity. The ongoing threat of funding removal was described by one administrator as community "bullying". Conclusions Processes of health promotion funding, and even standard processes of program scale-up and readiness assessment, risk underestimating the range of resources that are fundamental for community health improvement, particularly among disadvantaged communities. Funders should design ways to resource communities so that there is constant attention to and coaching of critically important diverse processes of resource growth, independent of program-specific funds.